Peningkatan Hasil Belajar Matematika Materi Penjumlahan Bersusun Panjang Tiga Bilangan Melalui Media Papan Kantong pada Siswa Kelas II SDN Lidah Wetan IV Surabaya - Nada Febiola; Sri Hartatik; Muslimin Ibrahim; Syamsul Ghufron (ENGGANG: Jurnal Pendidikan, Bahasa, Sastra, Seni, dan Budaya, 2024)
The aim of the study was to improve the learning outcomes of three-digit long addition in the placement of unit, tens, and hundreds values ​​in mathematics using pocket board media for class II students at SDN Lidah Wetan IV Surabaya. This type of research is Classroom Action Research (CAR), which includes several stages, namely planning, implementing or observing, and reflecting on each cycle. The subjects of this study were 20 students of class II at SDN Lidah Wetan IV Surabaya, consisting of 9 boys and 11 girls. The technique used is data collection techniques by carrying out several stages, namely observation, testing, and documentation. From the results of the study, it was shown that the application of pocket board media with addition material in long three-digit sums on the placement of unit values, tens, and hundreds can improve student learning outcomes in class II at SDN Lidah Wetan IV Surabaya. When no action was given, the learning value of the addition material in long three-digit additions in the placement of unit, tens, and hundreds values ​​in mathematics only 3 students (15%) achieved KKM. In the first cycle of action, there was a slight increase in student learning outcomes in mathematics, namely 15 students (75%), then followed by the second cycle of action, there was another increase, namely as many as 18 students (90%).